PELATIHAN MENGOMPOS SAMPAH ORGANIK DI KELURAHAN KALIBEBER KABUPATEN WONOSOBO - nila amania; Rohatun Nihayah; Linda Ikawati; Nur Fatimah; Zahra Maulida Lubna (Universitas Mataram, 2026)
Organic waste management remains a major challenge in many regions, including Kalibeber Village, Wonosobo Regency, where household organic waste is generally discarded without proper processing, resulting in accumulation at the Final Disposal Site (TPA). This community service program aimed to equip residents, particularly members of the PKK RT 05 RW 11 Munggang Bawah, with knowledge and skills in processing organic waste into compost. The implementation methods included needs assessment, socialization, training, and evaluation through pre-test and post-test. A total of 40 participants took part in the training, which was conducted through a combination of lectures, hands-on practice, and the provision of household composting equipment. The evaluation results indicated a significant improvement in participants’ knowledge, from 35–50% in the pre-test to 80–90% in the post-test. The highest improvement was observed in the understanding of the benefits of composting (50%) and the basic techniques of compost production (48%). These findings demonstrate that participatory-based training is effective in enhancing environmental literacy, strengthening practical skills in organic waste management, and fostering sustainable practices at the household level. Consequently, this program contributes to reducing the volume of waste disposed of at the TPA while supporting the creation of a cleaner, healthier, and more productive community environment.